Elevated temperature thermal properties of fire protective boards and insulation materials for light steel frame systems. (November 2021) - Steau, Edward; Mahendran, Mahen
Abstract: New materials are increasingly used in the construction of cold-formed Light gauge Steel Frame (LSF) systems to achieve lightweight, more durable and fire resistant building systems. However, these materials are being used without good knowledge and understanding of their elevated temperature thermal properties. Hence a thorough investigation of the elevated temperature thermal properties was conducted for a range of building materials used in the LSF systems of Australia, New Zealand and Europe. Thermal property tests were conducted on gypsum plasterboards, calcium silicate boards, magnesium oxide boards, perlite boards, insulation materials and structural plywoods, totalling 21 potential LSF components. The thermal properties of specific heat at constant pressure, relative density, thermal conductivity and thermal diffusivity were determined using differential scanning calorimetry, thermogravimetric analysis and laser flash analysis and the guidelines of ASTM standard test methods. This paper presents the results of the elevated temperature thermal properties of a range of building materials used in the LSF systems. This advanced knowledge and understanding of the elevated temperature thermal properties will allow accurate predictions of the fire resistance of LSF systems using appropriate numerical and fire design methods and facilitate the development of improved LSF systems with enhanced fire resistance levels. Several materials such as gypsum plasterboards, calcium silicate boards, perlite board and rockwool fibre insulation have been identified to be suitable for use in LSF systems because of their high specific heat, low thermal conductivity, reduced mass loss and low bulk density. Highlights: Investigated the elevated temperature thermal properties of 21 components used in light steel frame systems. Included specific heat, relative density, thermal conductivity and thermal diffusivity. Observed similar thermal properties for gypsum plasterboards made with different compositions. Identified suitable material types and characteristics for use in fire safe building construction. Proposed new thermal property models for boards, insulation and plywood materials.